Biofabrication of size-controlled ZnO nanoparticles using various capping agents and their cytotoxic and antitermite activity. Issue 6 (3rd May 2021) - Din, Muhammad Imran; Rani, Aneela; Hussain, Zaib; Khalid, Rida; Aihetasham, Ayesha; Mukhtar, Maria
ABSTRACT: Herein, monodisperse Zinc oxide nanoparticles (ZnO-NPs) have been fabricated by green adeptness with and without using capping agents. The different capping agents used include Syzygium cumini leaves extract, starch and cetyl trimethyl ammonium bromide (CTAB). The UV/Vis analysis showed an exciton absorption band in the range of 370–385 nm for all NPs. The SEM analysis showed that average particle size of all ZnO NPs was consistent with that which was calculated by using the Debye-Scherrer equation also by using effective mass model approach. The XRD analysis has confirmed their crystalline nature and monodisperse size distribution. The Photoluminescence spectrum (PL) indicated the presence of surface defects on ZnO nanoparticles, which are the` driving force in the efficient photocatalysis of brilliant green dye showing 89.33% degradation efficiency after 2 h. The plant-mediated ZnO NPs were an efficient antimicrobial agent against P. aeruginosa, E. coli, A.baumannii and K. pneumoniae strains; however, all fungal strains including P. chrysogenum, A. niger, T. citrinoviride, A. fumigatus were resistant to ZnO NPs at all concentrations. Furthermore, they showed a strong antitermite activity against Heterotermes indicola workers and soldiers with a 100% mortality rate in 24 h.